GAMBARAN PENGETAHUAN DAN PENDIDIKAN TENTANG KEIKUTSERTAAN SUAMI MENJADI AKSEPTOR KB DI WILAYAH PUSKESMAS KAMPUNG BALI KOTA BENGKULU - Yulianti, Syami (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
KB (Family Planning) is an effective way to stop the high rate of population growth, the number of people in Indonesia in 2013 amounted to 248 422 956, those inhabitants number increases relatively quickly. The need policies to regulate or limit the number of birth can be addressed births, the percentage of couples use contraception at fertile age (EFA) especially husband was the IUD (3.5%), implants (4.3%), MOP (0.1 %), MOW (2.3%), pills (13.9%), injections (34.3), condoms (0.8%), and Natural (0.3%). Male contraception percentage is still low. Objective To know the knowledge and education about the husband's participation become family planning acceptors in Kampung Bali PHC in the city of Bengkulu. The research was a descriptive with accidental sampling technique, the number of samples used were 100 couples of childbearing age especially husbands on January 8, 2015 at Kampung Bali PHC in the city of Bengkulu. The results of this research indicated that the majority (61%) of respondents had less knowledge level and most (71%) were lower educated. Conclusions that can be drawn from this research was the husband's level of knowledge and education in the area of Kampung Bali PHC in Bengkulu city on the participation of a husband being acceptors was still relatively low. Suggestion: it is expected the health workers to provide better information about family planning, especially the use of condoms KB and MOP to reduce the rate of population growth.